Human sperm tsRNA as potential biomarker and therapy target for male fertility. Issue 2 (February 2021) - Chen, Xiaoxu; Sun, Qian; Zheng, Yi; Liu, Zidong; Meng, Xiangqian; Zeng, Wenxian; Lu, Hongzhao
Abstract : Infertility caused by male factors is routinely diagnosed by assessing traditional semen parameters. Growing evidence has indicated that the tsRNAs carried in sperm act as epigenetic factors and potential biomarkers for the assessment of sperm quality. We recently demonstrated that tRNA Gln-TTG derived small RNAs played notable roles in the first cleavage of a porcine embryo. However, the function of human sperm tRNA Gln-TTG derived small RNAs as a diagnostic biomarker and its role in early embryo development remains unclear. In this study, we found that human sperm tRNA Gln-TTG derived small RNAs were highly associated with sperm quality. By microinjecting the antisense sequence into human tripronuclear (3PN) zygotes followed by single-cell RNA-sequencing, we found that human sperm tRNA Gln-TTG derived small RNAs participated in the development of a human embryo. Furthermore, Gln-TTGs might influence embryonic genome activation by modulating noncoding RNA processing. These findings demonstrated that human sperm tRNA Gln-TTG derived small RNAs could be potential diagnostic biomarkers and could be used as a clinical target for male infertility.